van 2de naar 3de dimensie. - Galerie de Vonk, Bussum (Bussum : Galerie de Vonk, 1983)
Toscani, Bep ; Oosterveld, Monica ; Luymes, Brita ; Chronis, Jorgos ; de Beus, Jan ; Reijenga, Corrie ; Löwenstein, Ernst ; Smit, Willem ; van Stuivenberg, Annie ; Loos, Renée ; Cornelissen, Hans
van 2de naar 3de dimensie, Galerie de Vonk, Bussum, 8 oktober t/m 12 november 1983
boek